A multicenter prospective randomized controlled trial for preoperative biliary drainage with uncovered metal versus plastic stents for resectable periampullary cancer. (16th August 2020) - Cho, Jae Hee; Yoon, Yoo‐Seok; Kim, Eui Joo; Kim, Yeon Suk; Cho, Jai Young; Han, Ho‐Seong; Park, Yeon Ho; Shin, Dong Woo; Lee, Jong‐chan; Hwang, Jin‐Hyeok; Kim, Jaihwan
Abstract: Background/Purpose: Although routine preoperative biliary drainage (PBD) in patients with distal malignant biliary obstruction is generally not recommended, there are still various situations where it may be necessary. The current study aims to compare the uncovered self‐expandable metal stent (uSEMS) and plastic stent (PS), where PBD may be necessary. Patients and Methods: In this multicenter prospective randomized study, patients with resectable periampullary cancer with cholangitis, deep jaundice, or expected long waiting time for surgery were included. PBD was performed endoscopically, but percutaneous drainage was allowed if the initial endoscopic drainage was not feasible. The primary outcome was the reintervention rate; the secondary outcomes were the complication rates, rate of decrease of total bilirubin, waiting time for surgery, and postoperative hospital stay. Results: Of the 60 enrolled patients, 53 were included for analysis (26 PS and 27 uSEMS). Common bile duct cancer was the most common (27, 50.9%), followed by pancreatic head cancer (20, 37.7%). Regarding PBD indication, 36 (67.9%) had cholangitis and 21 (39.6%) had a total bilirubin level of more than 10 mg/dL at randomization; 10 (18.9%) were included due to delayed surgery by more than 7 days. Fifty (94.3%) patients received pancreaticoduodenectomy, and one (1.9%) patient received palliative hepaticojejunostomy. The median waiting time for surgery was 11.0 days. There was no difference in the reintervention rate (3.8% and 3.8% in PS and uSEMS, P  > .999), PBD‐related complication rate (23.1% and 22.2%, P  > .999), PBD‐ or surgery‐related complication rate (57.7% and 48.1%, P  = .674), and the rate of decrease of total bilirubin ( P  = .541). The median hospital stay after surgery was 13.0 days without significant difference. Conclusion: For patients who received surgery within the first 2 weeks from receiving PBD, there was no superiority of uSEMS to PS. According to the expected waiting time for surgery, selective approach for stent choice should be considered. Abstract : Highlight In this prospective randomized trial, Cho and colleagues demonstrated no superiority of self‐ expandable metal stents over plastic stents for patients with resectable periampullary cancer who received surgery within 2 weeks after preoperative biliary drainage. Considering the cost, stent selection should be made according to the expected waiting time for surgery.